Biomechanical multibody knee model with condyle contact : modeling, simulation and analysis - Ribeiro, Ana Barros (2011)
Over the last decades, the study of human body motion as a multibody system has undergone enormous developments. In a broad sense, most of the research in simulation of human tasks is based on the assumption that the human joints constraining the relative motion of the anatomical segments are ideal joints. However, this assumption fails to capture obvious physical properties of the natural human articulations. The purpose of this work is to develop a computational multibody model able to capture some of the basic properties of the knee joint and simulate human gait during the stance phase including the kinetics of the real knee.